ESCHERICHIA COLI BACTERIA DETECTION IN DRINKING WATER DEPOTS BUNGO DISTRICT - Titis Wulandari; Randi Eka Putra; Tri Wera Agrita (BIOEDUKASI, 2021)
Water is a very important component in life, such as the use of water as drinking water, all living things, both humans, animals, and plants, need water. Part of the human body consists of fluids, so water helps the body to work to carry nutrients from the stomach to all parts of the body. So that a hygienic water source is needed, through a processing process first until the water meets health requirements. The purpose of this study was to detect the presence of Escherichia coli bacteria in drinking water depots in two sub-districts in Bungo Regency, namely (Rimbo Tengah, Pasar Muara Bungo). The test was carried out at the Fish Quarantine Station and Quality Control Laboratory of Class 1 Jambi. Direct sampling with sterile bottles. The sample testing method uses the Most Probable Number (MPN) test with SNI ISO 9308-1:2014. Direct sampling with sterile bottles. The sample testing method uses the Most Probable Number (MPN) test with SNI ISO 9308-1:2014.